Therapeutic potential of triptolide in autoimmune diseases and strategies to reduce its toxicity - Yaxin Cheng; Yonghua Zhao; Ying Zheng (BMC, 2021)
Abstract With the increasing epidemiology of autoimmune disease worldwide, there is an urgent need for effective drugs with low cost in clinical treatment. Triptolide, the most potent bioactive compound from traditional Chinese herb Tripterygium Wilfordii Hook F, possesses immunosuppression and anti-inflammatory activity. It is a potential drug for the treatment of various autoimmune diseases, but its clinical application is still restricted due to severe toxicity. In this review, the pharmacodynamic effects and pharmacological mechanisms of triptolide in autoimmune diseases are summarized. Triptolide exerts therapeutic effect by regulating the function of immune cells and the expression of cytokines through inflammatory signaling pathways, as well as maintaining redox balance and gut microbiota homeostasis. Meanwhile, the research progress on toxicity of triptolide to liver, kidney, reproductive system, heart, spleen, lung and gastrointestinal tract has been systematically reviewed. In vivo experiments on different animals and clinical trials demonstrate the dose- and time- dependent toxicity of triptolide through different administration routes. Furthermore, we focus on the strategies to reduce toxicity of triptolide, including chemical structural modification, novel drug delivery systems, and combination pharmacotherapy. This review aims to reveal the potential therapeutic prospect and limitations of triptolide in treating autoimmune diseases, thus providing guiding suggestions for further study and promoting its clinical translation.